Mascot - Waters, Charles, 1973-; Sorell, Traci (Charlesbridge, 2023)
"In Rye, Virginia, just outside Washington, DC, people work hard, kids go to school, and football is big on Friday nights. An eighth-grade English teacher creates an assignment for her class to debate whether Rye's mascot should stay or change. Now six middle schoolers--all with different backgrounds and beliefs--get involved in the contentious issue that already has the suburb turned upside down with everyone choosing sides and arguments getting ugly. Told from several perspectives, readers see how each student comes to new understandings about identity, tradition, and what it means to stand up for real change" --